2019
DOI: 10.1002/hed.25836
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trismus in patients with head and neck cancer: A systematic review with meta‐analysis

Abstract: Background The purpose of this systematic review and meta‐analysis was to determine the prevalence of trismus in patients with head and neck cancer. Methods Four electronic databases were searched: Cochrane Library, MEDLINE, EMBASE, and Web of Science up to April 2018. Level of evidence was assessed based on Oxford Centre for Evidence‐based Medicine. Publications were restricted to prospective cohort studies (n = 15), randomized clinical trials (n = 3), and cross‐sectional studies (n = 5) reporting on trismus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Early surgery or radiotherapy can achieve good results, but most patients with head and neck squamous cell carcinoma have exhibited cervical lymph node metastasis or distant metastasis at the first diagnosis. Although surgery plus radiotherapy or chemotherapy can delay the progression of the disease, the patients with stage III/IV do not be improved the long-term survival rate 19 . Therefore, early diagnosis and early treatment are the key to the treatment of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgery or radiotherapy can achieve good results, but most patients with head and neck squamous cell carcinoma have exhibited cervical lymph node metastasis or distant metastasis at the first diagnosis. Although surgery plus radiotherapy or chemotherapy can delay the progression of the disease, the patients with stage III/IV do not be improved the long-term survival rate 19 . Therefore, early diagnosis and early treatment are the key to the treatment of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Treating HNSCC patients with surgery, instead of CRT, means they avoid the typical complications of RT and CT; xerostomia, osteoradionecrosis, mucositis, sepsis and trismus ( 2 , 4 , 9 , 23 ). A recent study ( 24 ) reported an overall survival rate of 84.9% and a low rate of xerostomia in 442 patients who received intense modulated radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of limitation in mouth opening in patients with oral-maxillofacial malignant tumors ranges from 8% to 62% (13). The patients were a majority male, with an average age from 53.5 to 65.9 years old (14,15). It may be related to the tumor clinical stage, tumor site, treatment(s) used, radiotherapy site, radiotherapy dose, radiotherapy type, follow-up time after treatment and sample variation.…”
Section: The Prevalencementioning
confidence: 99%